Lådvinsalkoholism: Kategorier som meningsgivare - Börjesson, Mats (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2004)
Addiction to alcohol is a well known problem category in our culture. During the last years, we have in Sweden seen an extension of that category; concerning the package "Bag-in-box". This article claims that categorisation is action and that it is an interesting field for research — in its own right. To get a story which is credible, the narrator have to present reality in certain ways — it has to be told by the right person, and it must be put in the proper way in order to be believed in. For this we have a number of ingredients and the article focuses on some of them, such as extreme-case formulations, addiction metaphors, category entitlement, and membership categorisation. The story about bag-in-box alcoholism shows many of these, which makes us believe in the severe- and realness of this problem.